Leapfrogging into Digital Credit: The Trade-off between Financial Inclusion and Portfolio Risk in Sub-Saharan Africa: A Comparative Analysis of Kenya and Ethiopia - Belay Sitotaw Goshu; Muhammad Ridwan (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2026)
The rapid proliferation of mobile-based lending across Sub-Saharan Africa has generated a fundamental tension: digital credit promises financial inclusion at scale yet carries inherent portfolio risks that threaten lender stability and borrower welfare. This study examines this inclusion-risk trade-off through a comparative analysis of Kenya, a mature digital credit market, and Ethiopia, an emerging latecomer with significant leapfrogging potential. Drawing on bank-level loan performance data, regulatory frameworks, and institutional analysis spanning 2014–2025, the study documents Kenya's "develop first, regulate later" trajectory, which achieved remarkable inclusion, 5.5 million borrowers, and Sh76.8 billion in disbursements but at the cost of a micro-loan default crisis, with loans below KES 1,000 defaulting at 83.1 percent. Four determinants-loan appraisal, borrowing costs, disbursement management, and repayment terms mediate this trade-off. Ethiopia, by contrast, has adopted a proactive regulatory framework but constrained inclusion through a bank-account mandate that excludes the unbanked majority. Early risk indicators, unsecured lending at scale, fee opacity, and emerging defaults suggest vulnerabilities are already present. The comparative analysis yields five stylized facts and five policy recommendations for latecomer economies: recalibrate credit access, strengthen consumer protection, invest in financial infrastructure, adopt regulatory sandboxes, and enhance supervision. The findings extend leapfrogging theory, demonstrating that technological leapfrogging does not automatically imply regulatory leapfrogging. Ethiopia has a narrow window to integrate innovation, inclusion, and stability from the outset, offering lessons for emerging digital finance markets worldwide.